Islamic Education in the Development of Traditions and Educational Institutions - Hidayatullah, Agus; Nasyar, Abidin; Rudjikartawi, Erdi (International Journal on Advanced Science, Education, and Religion, 2025)
This study aims to analyze the role of Islamic education as a central force in preserving, revitalizing, and developing Islamic scholarly traditions and establishing solid educational institutions. This study is driven by observations of socio-cultural dynamics in which Islamic education functions not only as a means of transmitting religious knowledge, but also as an agent of civilization (development) that is relevant to contemporary challenges.The methods used are literature study and qualitative analysis, tracing the history, philosophy, and practices of Islamic education in various settings, ranging from traditional Islamic boarding schools/madrasas to modern Islamic universities. The main focus is to identify how the curriculum, teaching methods, and institutional environment of Islamic education contribute to the transmission of values (morals), thought (philosophy), and practice (fiqh/amaliah) that are the pillars of Islamic civilization and the development of institutions that adapt structurally and managerially to remain relevant, accountable, and competitive in the era of globalization. The results of the study show that the success of developing traditions and institutions is highly dependent on the ability of Islamic education to maintain a balance between asalah (authenticity/tradition) and mu'asarah (contemporaneity/innovation). Successful institutions are those that integrate the strengthening of scientific traditions with the adoption of modern management, thereby producing graduates who possess both spiritual and scientific depth as well as the professional competencies needed by society.